1998
DOI: 10.1176/ajp.155.8.1009
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Induced Limbic Cortical Activation in the Human Brain: A Functional MRI Study

Abstract: The identified brain regions have been previously shown to participate in the reinforcing, mood-elevating, and cognitive properties of other abused drugs such as cocaine, amphetamine, and opiates, suggesting that nicotine acts similarly in the human brain to produce its reinforcing and dependence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
258
2
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 443 publications
(292 citation statements)
references
References 28 publications
24
258
2
7
Order By: Relevance
“…The dose of nicotine administered might also have been a contributor to the small change in BP we observed. We elected to keep the dose of nicotine around 0.03 mg/kg, because this was a dose that Stein et al (1998) reported to be well tolerated when administered as a 1 min i.v. bolus in human smokers (a cigarette contains between 0.01 and 0.03 mg/kg nicotine for a 70 kg person).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of nicotine administered might also have been a contributor to the small change in BP we observed. We elected to keep the dose of nicotine around 0.03 mg/kg, because this was a dose that Stein et al (1998) reported to be well tolerated when administered as a 1 min i.v. bolus in human smokers (a cigarette contains between 0.01 and 0.03 mg/kg nicotine for a 70 kg person).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no statistically significant difference between the two methods of tracer administration (B/I and bolus), we believe the B/I technique offers some advantages: it is more economical because it provides the same information with a single [ 11 C]raclopride synthesis; calculation of BP images is simplified; values outside the immediate area of the basal ganglia are less noisy than with images created with SRTM, potentially enabling analysis of BP changes over the whole brain; even within the basal ganglia the statistical quality of the images is improved; and it is less sensitive to changes in blood flow (Carson, 2000) induced by nicotine (Domino et al, 2000;Stein et al, 1998;Zubieta et al, 2001). Although these arguments support the use of the B/I method for studies of nicotine-induced DA release, this decision has to be weighted according to the characteristics of the tracer and the displacement expected.…”
Section: Discussionmentioning
confidence: 99%
“…In studies examining regional activity responses to nicotine or smoking, the most common findings are relative increases in activity in the prefrontal cortex (including the dorsolateral prefrontal cortex, and inferior frontal, medial frontal, and orbitofrontal gyri) (Domino et al, 2000b;Rose et al, 2003;Stein et al, 1998), thalamus (Domino et al, 2000a;Domino et al, 2000b;London et al, 1988a,b;Stein et al, 1998;Zubieta et al, 2001), and visual system (Domino et al, 2000a;Domino et al, 2000b;London et al, 1988a,b) (Jed Rose, Personal Communication). Additionally, a Xe 133 inhalation study reported increases in frontal lobe and thalamic blood flow in smokers who smoked a cigarette (Nakamura et al, 2000).…”
Section: Brain Activity Responses To Nicotine/cigarette Administrationmentioning
confidence: 99%
“…In pharmacological fMRI studies to date, the temporal profile of the drug's effect has been assumed. The assumption has either been implicit in comparing fMRImeasured brain activity before and after administration (Breiter et al, 1997;Coull et al, 2001;Furey et al, 2000;Hariri et al, 2002;Honey et al, 1999;Kimberg et al, 2001;Kleinschmidt et al, 1999;Mattay et al, 2000;Thiel et al, 2001Thiel et al, , 2002, or the assumption has been more explicit in incorporating pre-existing pharmacokinetic parameters into the analysis of fMRI data (Stein et al, 1998;Bloom et al, 1999;Wise et al, 2002). In either case, the aim has been to simply identify drug-induced changes in brain activity.…”
Section: Introductionmentioning
confidence: 99%